Experimental and theoretical investigation of the molecular and electronic structure of N?-benzylidene-N-[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-chloro-acetic acid hydrazide - Demir, Sibel; Dincer, Muharrem; Cukurovali, Alaaddin; Yilmaz, Ibrahim (Wiley, 2012)
The title compound, N'-benzylidene-N-[4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-chloro-acetic acid hydrazide, has been synthesized and characterized by elemental analysis, IR, 1H and 13C NMR, and X-ray single crystal diffraction. The compound crystallizes in the orthorhombic space group P 21 21 21 with a = 5.8671 (3) angstrom, b = 17.7182 (9) angstrom, and c = 20.6373 (8) angstrom. Moreover, the molecular geometry from X-ray experiment, the molecular geometry, vibrational frequencies, and gauge-including atomic orbital 1H and 13C chemical shift values of the title compound in the ground state have been calculated by using the HartreeFock and density functional methods (B3LYP) with 6-31G(d) and 6-31G(d,p) basis sets. The results of the optimized molecular structure are exhibited and compared with the experimental X-ray diffraction. Besides, molecular electrostatic potential, Frontier molecular orbitals, and thermodynamic properties of the title compound were determined at B3LYP/6-31G(d) levels of theory. (C) 2011 Wiley Periodicals, Inc. Int J Quantum Chem, 2012
Keywords: X-ray structure determination; IR and NMR spectroscopy; Hartree-Fock; density functional method; molecular electrostatic potential